Pemanfaatan Daun Kersen (Muntingia calabura L.) Dan DaunSirsak Dalam Pembuatan Teh Dengan Penambahan Pemanis Daun Stevia - Yustika, Evira; , Dr. Nanik Suhartatik, S.TP. M.P (2015)
Cherry leaf can be use as tea material because of its flavonoids, triterpenoids, alkaloids, saponins, and steroids. Mean while soursop leaf contain acetogenins, annocatacin, annocatalin, annohexocin, annonacin, annomuricin, anomurine, anonol, caclourine, gentisic acid, gigantetronin, linoleic acid, and muricapentocin. In addition to using natural sweetener using stevia leaf containing compounds and dulcosida rebaudiosida steviosida. The purpose of this study was to compare the cherry leaf and soursop leaf that will provide antioxidant activity and total phenolic highest in the manufacture of tea with the addition of sweetener stevia leaf. The research method using completely randomized design with two factors. The first factor was the ratio of cherry leaf with soursop leaf (A0) 0%: 100%, (A1) 25%: 75%, (A2) 50%: 50%, (A3) 75%: 25%, (A4) 100% : 0%. The second factor is weight of stevia leaf (E1): 1%, (E2): 2%. Can be seen from the test results that the highest ratio of antioxidant activity of the sample A0E1, while the highest ratio of total phenol from sample A0E2. The antioxidant activity of leaf cherry and soursop leaf with the addition of sweetener stevia leaf is found that the highest antioxidant activity A0E1 sample with 52.89%. The highest of total phenol A0E2 sample with 49.73 mg as.galat/100 ml.